Femoral Notch Anatomy and Tibial Slope in Anterior Cruciate Ligament Injuries: An Observational Study - Jayant Bhagwan Mishra; Sunil Singh Thapa; Kaushal Raj Kafle; Sundar Suwal; Arjun Prasad Lamichhane (Journal of Nepal Medical Association, 2025)
Introduction: The anterior cruciate ligament is a primary knee stabilizer frequently injured during sports activities, with risk factors including intrinsic anatomical variations. These anatomical factors vary by race, sex, and body structure. The study aimed to identify anatomical risk factors for anterior cruciate ligament injury in the Nepalese population using magnetic resonance imaging. Methods: This observational comparative study was conducted from December 2021 to July 2023 after obtaining ethical clearance (Reference number: 286(6-11) E2 078/079). Magnetic resonance imaging scans of 122 knees (61 anterior cruciate ligament injured and 61 intact) were analyzed. Intercondylar femoral notch width, notch width index, notch angle, medial and lateral posterior tibial slopes were measured. Notch shapes (A, U, W) were classified. Independent t-test and chi-square test were used for comparing continuous and categorical variables, respectively. The Statistical Package for the Social Sciences (version 26) was used for analysis. Results: The anterior cruciate ligament injured group showed significantly smaller mean notch widths (coronal: 1.90±0.28cm, axial: 1.98±0.30cm), lower notch width indices (coronal: 0.27±0.03, axial: 0.28±0.04), and more acute notch angles (coronal: 49.89±6.12°, axial: 48.70±6.67°) compared to controls (all p<0.05). Both medial (11.23±5.21° vs 8.76±4.76°) and lateral (11.24±5.33° vs 8.76±4.94°) posterior tibial slopes were significantly steeper in injured knees (p<0.01). Type A notches were more common in injured knees. Conclusions: Smaller femoral notches, lower notch indices, more acute notch angles, and steeper posterior tibial slopes were associated with anterior cruciate ligament injuries.